Advances in Smart Coating Technologies for Wind Turbine Blade Protection: A Focus on Self-Healing and Anti-Erosion Performance - Mohamad Alsaadi; Leon Mishnaevsky; Edmond Francis Tobin; Declan M. Devine (Journal of Marine Science and Engineering, 2025)
Leading-edge erosion (LEE) of wind-turbine blades, driven primarily by rain erosion, particulate erosion, and environmental ageing, remains one of the most pervasive causes of performance loss and maintenance cost in offshore and onshore wind farms. Self-healing coatings, which autonomously or semi-autonomously restore barriers and mechanical function after damage, promise a paradigm shift in blade protection by combining immediate impact resistance with in-service reparability. This review surveys the state of the art in self-healing coating technologies (intrinsic chemistries such as non-covalent interactions or dynamic covalent bonds; extrinsic systems including micro/nanocapsules and microvascular networks) and evaluates their suitability for anti-erosion, mechanical robustness, and multifunctional protection of leading edges. The outcomes of theoretical, experimental, modelling and field-oriented studies on the leading-edge protection and coating characterisation identify which self-healing concepts best meet the simultaneous requirements of toughness, adhesion, surface finish, and long-term durability of wind blade applications. Key gaps are highlighted, notably trade-offs between healing efficiency and mechanical toughness, challenges in large-area and sprayable application methods, and the need for standardised characterisation and testing of self-healing coating protocols. We propose a roadmap for targeted materials research, accelerated testing, and field trials. This review discusses recent studies to guide materials scientists and renewable-energy engineers toward promising routes to deployable, multifunctional, self-healing anti-erosion coatings, especially for wind-energy infrastructure.

Exploring the role of polysaccharides from macroalgae in shaping gut microbiome and promoting anti-obesity outcomes - Mehdi Amiri Goushki; Zahra Kharat; Gustavo Waltzer Fehrenbach; Emma J. Murphy; Declan Devine; Noel Gately; Evert Fuemayor (Food Hydrocolloids, 2025)